İslam fütuhatının kalıcılığı : Dımaşk'ın fethi ve İslamlaşması (h. 1. yy) - Taşdemir, Elif (My University, 2025)
İslam fütuhatının kalıcılığı : Dımaşk'ın fethi ve İslamlaşması (h. 1. yy) Bu çalışma, tarihte bir dönüm noktası olan erken dönem İslam fütuhatının başarılı olmasını sağlayan faktörleri, Müslümanların bu fetihler sırasındaki temel motivasyonlarını ve fethedilen bölgelerde siyâsi hâkimiyeti kalıcı kılmak ve İslam’ı yaymak adına yapılmış olan askerî, idarî, ekonomik ve sosyal düzenlemeleri; Hz. Ömer döneminde Ebû Ubeyde b. Cerrâh komutanlığında fethi gerçekleşen Dımaşk şehri örneği üzerinden incelemektedir. Çalışmanın ilk bölümünde Hz. Ebû Bekir’in, Hz. Peygamber’in (sav) vefatının ardından onun hazırlatmış olduğu Üsâme ordusunu Suriye bölgesine göndermesiyle ilk adımları atılmış olan Şam bölgesi fetihlerinden Dımaşk şehrinin fethi ele alınmıştır. Hz. Ebû Bekir’in Şam bölgesinde Bizans İmparatorluğunun askerî düzenini göz önünde bulundurarak askerî strateji belirmesinin ve bu doğrultuda bölgeye dört komutan tayin edip orduları dört farklı bölgeye göndermesinin Şam cephesinde Müslümanların başarısında önemli etkisi olduğu görülmüştür. Sulh yoluyla fethi gerçekleşen Dımaşk şehrinde fethin akabinde Müslümanların yapmış oldukları askerî, idaerî ve ekonomik düzenlemelerin ve iskân politikasının şehirde Müslümanların siyasî hâkimiyetlerinin istikrar kazanmasında ve İslam’ın yayılmasında büyük önemi haiz olduğu sonucuna varılmıştır.

The permanance of ıslamic conquests : the conquest Of damascus and its Islamization (h. 1st century) This study examines the key factors that contributed to the success of the early Islamic conquests, which marked a turning point in history. It explores the primary motivations of Muslims during these conquests and analyzes the military, administrative, economic, and social arrangements implemented to establish permanent political authority and to spread Islam in the conquered regions. This research specifically focuses on the city of Damascus, which was conquered during the caliphate of ʿUmar ibn al-Khaṭṭāb under the command of Abū ʿUbayda ibn al-Jarrāḥ. In the first part of the study, the conquest of Damascus—within the broader context of the conquests of the greater al-Shām region, which were initiated by the dispatch of the Usāmah ibn Zayd expedition to the Syrian front by Abū Bakr following the passing of the Prophet Muḥammad (peace be upon him)—is examined. It has been observed that Abū Bakr's strategic assessment of the Byzantine military organization in the region, and his decision to appoint four commanders and send separate armies to four different fronts, played a significant role in the Muslim successes on the Syrian front. In Damascus, which was conquered through a treaty (sulḥan), the military, administrative, and economic regulations, as well as the settlement policies implemented by the Muslims in the aftermath of the conquest, were found to have played a crucial role in consolidating stable political authority and facilitating the spread of Islam in the city.
The permanance of ıslamic conquests : the conquest Of damascus and its Islamization (h. 1st century)
Keywords: Conquests; Damascus; Dımaşk; Fütuh; History of Islamic religion; Hulefâ-yi Râşidîn; Islamic History; İslam dini tarihi; İslam Tarihi; Rightly Guided Calips; Şam; Territory of al-Shâm